تقدير صدق بنية التعلم التنظيمي وفقا لنموذج سينج بتوظيف النمذجة - ساخي, بوبكر; تيغزة, أمحمد (جامعة الوادي University of Eloued, 2018)
لملخص: إستهدف البحث إختبار صدق بنية مفهوم التعلم التنظيمي وفقا لنموذج سينج (1990). إن مفهوم التعلم التنظيمي– وفقا لنموذج سينج ـ ينطوي على خمسة أبعاد أو عوامل وهي: التفكير النظمي، التمكن الشخصي، النماذج الذهنية، الرؤية المشتركة، وتعلم الفريق. هذه الأبعاد الخمسة تنتمي بدورها إلى عامل أعلى عام يدعى بالتعلم التنظيمي. كما استهدف البحث مقارنة هذه البنية الهرمية للتعلم التنظيمي بنوعين آخرين منافسين من بنيات مفهوم التعلم التنظيمي: النموذج العاملي الأحادي البعد، والنموذج العاملي الخماسي غير الهرمي. اشتملت العينة على (276) من موظفي المؤسسة الوطنية للكهرباء والغاز بالغرب الجزائري (مؤسسة سونلغاز)، أستخدم إستبيان التعلم التنظيمي لسينج. واستعمل التحليل العاملي التوكيدي باستخدام حزمة.وأظهرت النتائج أن البنية الهرمية لمفهوم التعلم التنظيمي وفقا لنموذج سينج إنطوى على مطابقة جيدة للبيانات من جهة، ومن جهة أخرى تفوق على النموذجين الآخرين المنافسين: النموذج العاملي الأحادي البعد، والنموذج العاملي الخماسي غير الهرمي. وأختتمت الدراسة بمناقشة وبعض التوصيات.ABSTRACT:The aim of the present research was to validate Singe’s model concerning the structure of organizational learning. According to Singe (1990) framework, the concept of organizational learning contains five dimensions (domains): Systematic thinking, Personal mastery, Mental model, Shared vision, and Team learning. The afore-five factors pertain to a higher factor named organizational learning. The validity of Singe hierarchical multidimensional model of organizational learning was examined in comparison with two competing models of organizational learning structure: One factor-model and a correlated (non-hierarchical) fivefactor model. The sample consists of 276 employees; and Singe’s organizational learning questionnaire was used. Confirmatory factor analysis, Through AMOS-22, was performed. Results indicate that the hierarchical structure of organizational learning fits well the data, and were more valid than the two competing models: One factor-model and a correlated (nonhierarchical) five-factor model. The study concluded with a discussion and recommendations.
والتحليل العاملي التوكيدي
مقال
Keywords: التعلم التنظيمي، نموذج سينج للتعلم التنظيمي، البنية العاملية الهرمية، صدق مفهوم التعلم التنظيمي: Organizational learning, Singe’s model of learning; Hierarchical model of Organizational learning; Validity